2015
DOI: 10.1158/1078-0432.ccr-14-1174
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Variation in Mature MicroRNA-499 Confers Unfavorable Prognosis of Lung Cancer Patients Treated with Platinum-Based Chemotherapy

Abstract: Purpose: This study was implemented to investigate the associations between SNP in mature microRNA (miRNA) sequence and lung cancer prognosis and to verify the function of those SNP.Experimental Design: Eight SNPs (rs3746444T>C in hsa-mir-499, rs4919510C>G in hsa-mir-608, rs13299349G>A in hsa-mir-3152, rs12220909G>C in hsa-mir-4293, rs2168518G>A in hsamir-4513, rs8078913T>C in hsa-mir-4520a, rs11237828T>C in hsa-mir-5579, and rs9295535T>C in hsa-mir-5689) were analyzed in a southern Chinese population with 576… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 52 publications
(53 reference statements)
2
24
0
Order By: Relevance
“…A recent meta-analysis showed that miR-499 rs3746444 polymorphism contributed to increased risk of many cancers (GG versus AA: OR = 1.24, 95% CI: 1.01-1.52; G versus A: OR = 1.11, 95% CI: 1.01–1.23) [32]. This is consistent with our results, which revealed that rs3746444 in mir-499 was significantly associated with increased risk of lung cancer, and the carriers of minor allele C have higher expression levels of mir-499 than those of major allele T. Very recently, Qiu et al [37] also reported that rs3746444 could contribute to poor prognosis by modulating cancer-related genes' expression and thus involve tumorigenesis and anti-chemotherapy. Furthermore, the in silico functional analysis of rs3746444 and rs4919510 was conducted by miRVaS: a tool to predict the impact of genetic variants on miRNAs [38].…”
Section: Discussionsupporting
confidence: 91%
“…A recent meta-analysis showed that miR-499 rs3746444 polymorphism contributed to increased risk of many cancers (GG versus AA: OR = 1.24, 95% CI: 1.01-1.52; G versus A: OR = 1.11, 95% CI: 1.01–1.23) [32]. This is consistent with our results, which revealed that rs3746444 in mir-499 was significantly associated with increased risk of lung cancer, and the carriers of minor allele C have higher expression levels of mir-499 than those of major allele T. Very recently, Qiu et al [37] also reported that rs3746444 could contribute to poor prognosis by modulating cancer-related genes' expression and thus involve tumorigenesis and anti-chemotherapy. Furthermore, the in silico functional analysis of rs3746444 and rs4919510 was conducted by miRVaS: a tool to predict the impact of genetic variants on miRNAs [38].…”
Section: Discussionsupporting
confidence: 91%
“…For instance, the hsa-let-7 family which regulates the cell cycle and the hsa-mir-200 family that induces cell death and cell proliferation were all differentially expressed in LN tumor samples[50]. Among the five unconfirmed miRNAs, hsa-miR-499 has been found that the rs3746444T> C polymorphism in its mature sequence could contribute to poor prognosis by modulating cancer-related gene expression and thus involve in the tumorigenesis of LN[51]. Besides, studies have shown that miR-103 was able to promote proliferation of small cell lung cancer cells through targeting MED26 mRNA 3ʹ-UTR[52].…”
Section: Resultsmentioning
confidence: 99%
“…We got the similar data that the expression of miR-499 don't have any statistical significance on clinicopathologic features in SCLC and NSCLC, but I/II stage with III/IV stage and differentiation degree in NSCLC. miR-499 could contribute to poor prognosis by modulating cancer-related genes' expression and thus involve tumorigenesis and anti-chemotherapy, which maybe a useful biomarker to predict lung cancer patients' prognosis (Qiu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…miR-486 directly targets components of insulin growth factor (IGF) signaling including insulin-like growth factor 1 (IGF1), IGF1 receptor (IGF1R), and phosphoinositide-3-kinase, regulatory subunit 1 (alpha) (PIK3R1, or p85a) and functions as a potent tumor suppressor of lung cancer both in vitro and in vivo (Peng et al, 2013). miR-499 could contribute to poor prognosis by modulating cancer-related genes' expression and thus involve tumorigenesis and anti-chemotherapy (Qiu et al, 2015). It may influence the expression of a series cancer-related genes that might be annotated to immunity and defense, cell growth, tumor invasion and metastasis, cancer stem cell, and cell death, although no available evidences supported any genes to be known or predicted target genes of miR-499.…”
Section: Introductionmentioning
confidence: 99%